2015
DOI: 10.1071/ch15062
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Observation of Triplet and Singlet Cyclopentane-1,3-diyl Diradicals in the Intersystem Crossing Process

Abstract: Intersystem crossing is an important chemical process. In this study, the rate constant of intersystem crossing, kISC ~3 × 107 s–1, for cyclopentane-1,3-diyl diradicals was unequivocally determined by the simultaneous observation of the decay process of the triplet diradical (λobs = 320 nm) and the growth process of the corresponding singlet diradical (λobs = 560 nm). The two spin states were directly observed using a long-lived singlet 2,2-dimethoxy-1,3-diphenylcyclopentane-1,3-diyl diradical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The lifetime of the singlet diradical S‐ DR16 was found to be 620±12 ns at 293 K (Figure S5 in the Supporting Information), which is much shorter than that of S‐ DR2 g , h with the macrocyclic system (Table ). As judged by the large lg A values of about 12, the decay of 580 nm species is spin‐allowed process to give the corresponding singlet products (Scheme ) . The activation energies of the first‐order decay process of DR2 g , h were found to be about 52–55 kJ mol −1 , which are close to the computed values for the ring‐closing reaction to the cis isomer of the ring‐closure product cis ‐ CP2 g (Table ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The lifetime of the singlet diradical S‐ DR16 was found to be 620±12 ns at 293 K (Figure S5 in the Supporting Information), which is much shorter than that of S‐ DR2 g , h with the macrocyclic system (Table ). As judged by the large lg A values of about 12, the decay of 580 nm species is spin‐allowed process to give the corresponding singlet products (Scheme ) . The activation energies of the first‐order decay process of DR2 g , h were found to be about 52–55 kJ mol −1 , which are close to the computed values for the ring‐closing reaction to the cis isomer of the ring‐closure product cis ‐ CP2 g (Table ).…”
Section: Resultssupporting
confidence: 67%
“…As judged by the large lg A valueso f about 12, the decay of 580 nm speciesi ss pin-allowed process to give the corresponding singlet products (Scheme 2). [22] The activation energies of the first-order decay process of DR2 g,h were found to be about 52-55 kJ mol À1 ,w hich are close to the computed values for the ring-closing reaction to the cis isomer of the ring-closure product cis-CP2 g ( Table 2). The negligible substituent effect of the meta substituents on the thermodynamic stabilization of the diradical was revealed by the similar absorption maxima of S-DR2 e,S -DR2 g,a nd S-DR16,w hich were found to be 575, 575, and 576 nm.…”
Section: Figuresupporting
confidence: 78%
“…Planar diradical pl-1 DR1 was generated by LFP of a degassed acetonitrile solution of AZ1 (0.33 mM, Abs 355 = 0.03) and Xan (0.50 mM, Abs 355 = 0.13) (Figure 5a). 48,49 Transient absorption spectra showed that the quenching of 3 Xan* was concomitant with the formation of pl-1 DR1 (λ max = 570 nm) (Figure 5a). The quenching rate constant (k q = 5.4 × 10 9 M −1 s −1 ) at 293 K in degassed acetonitrile was determined from the Stern−Volmer plot (Figure S10), showing that the decay of 3 Xan* was dominated by energy transfer from 3 Xan* to AZ1.…”
Section: Photochemical Denitrogenation Mechanism Of Az1mentioning
confidence: 99%
“…In this region, the activation parameters were obtained as Δ H ⧧ = 21.4 kJ mol –1 , Δ S ⧧ = −145.3 J K –1 mol –1 , and Δ G ⧧ = 58.2 kJ mol –1 at 253 K and Δ G ⧧ = 72.7 kJ mol –1 at 353 K. The large entropy contribution in the low-temperature region (iii) is reasonable because 9 is formed from triplet diradical T- 7 via the intersystem crossing process (ISC) from S- 7 (Scheme ). The spin-forbidden ISC processes are known to provide entropy control, whereby, in general, large negative entropy and small log A values are observed. , In the high-temperature region (i), the Gibbs energy for the ISC process becomes larger than the energy for another reaction pathway from S- 7a to 9aa . Thus, a dramatic temperature effect was observed for the product selectivity in the photodenitrogenation of 6a .…”
Section: Resultsmentioning
confidence: 99%